2016
DOI: 10.4038/cmj.v61i3.8347
|View full text |Cite
|
Sign up to set email alerts
|

Depressive disorder in patients attending the outpatient department of a tertiary care hospital in Colombo

Abstract: Introduction Lifetime prevalence of depression varies across countries and different populations. Depression is a common comorbidity of physical illness. Patients with depression are known to present with somatic symptoms. Depression is under-diagnosed in primary care settings.Objectives To estimate the prevalence of depression in patients attending the outpatient department (OPD) of a tertiary care hospital in the Western Province of Sri Lanka.Methods A cross-sectional descriptive study was conducted in the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The prevalence of depression in our study population was similar to the prevalence of depression reported among patients attending an outpatient department of a tertiary care hospital, Colombo (17). In comparison to our study, the prevalence of anxiety (17.6%) was similar and depression (8.5%) was lower in a previous study of clinic follow up patients with tuberculosis, conducted at the same hospital using the same rating scale (18).…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of depression in our study population was similar to the prevalence of depression reported among patients attending an outpatient department of a tertiary care hospital, Colombo (17). In comparison to our study, the prevalence of anxiety (17.6%) was similar and depression (8.5%) was lower in a previous study of clinic follow up patients with tuberculosis, conducted at the same hospital using the same rating scale (18).…”
Section: Discussionsupporting
confidence: 85%
“…A combination of tools including validated Sinhala version of the BDI, Zung Self-Rating Depression Scale (SDS), and consultant psychiatrist's clinical assessment using the Diagnostic Criteria for Research was used in the previous study while the depression scale used in Centre for Epidemiologic studies was used as the research tool in the latter. Another study which looked into the depressive disorders among patients attending the out-patient department in a tertiary care hospital in Colombo reported an overall prevalence of 22.4%, with females being more affected than males (25.4% versus 18.7%) and significant association between pain related presenting complaint [15]. All these studies show that there is a wide variation in the rate of depression among various populations suffering from chronic illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Either in the general population, diabetics, or chronic disease patients, females more likely to get MHD. [8,42] Current study also found that elderly diabetics who lived in an urban area are less likely to experience MHD (POR=0.75) compared to diabetics live in a rural area. Most of the elderly diabetics in this study population were living in an urban area (63.8%); however, the proportion of MHD among elderly diabetics more likely occur in rural areas.…”
Section: Discussionmentioning
confidence: 68%